Manajemen Kelas Berbasis Kearifan Lokal Di SD Muhammadiyah 24 Gajahan Surakarta - Setyaningrum, Iis, Drs. Achmad Fathoni, M.Pd (2017)
This research aims to know: 1) How to prepare class based on local wisdom in 24 SD Muhammadiyah elementary school Gajahan of Surakarta, 2) How is the implementation of classroom management based on local wisdom in 24 SD Muhammadiyah elementary school Gajahan of Surakarta, 3) How is the evaluation mechanism of classroom learning based on local wisdom in 24 SD Muhammadiyah elementary school Gajahan of Surakarta. This research is descriptive qualitative research. Informants in this study are principals, teachers grade I to class VI, and students class II, III, IV and VI. Data collection techniques by interview, observation and documentation. Data technique is analyzed by interactive analysis. Verify the validity of data using source triangulation and techniques. The results showed that how to prepare class based on local wisdom, among others 1) Preparing all facilities and infrastructure include: a) Preparing iqra ', b) Preparing iqra' grip students, c) Preparing data recapitulation iqra 'grip teacher, 2) Prepare study space Good, clean and conducive includes: a) Arranging wall hangings according to theme, b) Arranging seats, c) Setting light, 3) Using appropriate techniques, strategies and methods, 4) Creating study contracts. Implementation of classroom management based on local wisdom by: 1) Creating a fun learning atmosphere include: a) Invite students ice breaking, b) Invite students to sing, 2) Form team work, 3) Use of appropriate media, 4) The ability to connect the lesson with Curriculum and climate muhammadiyah, 5) Habituation using school supplies, 6) Understanding of the culture of local communities. The evaluation mechanism of classroom learning based on local wisdom is: 1) Strengthening about local cultural superiority, 2) Presence of rewards and punishment; 3) Increase the value of attitude, 4) Creating chemistry establish good communication